2021
DOI: 10.1371/journal.pone.0252441
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on hospital admissions and emergency department visits: A population-based study

Abstract: Background As a result of the novel coronavirus disease 2019 (COVID-19), there have been widespread changes in healthcare access. We conducted a retrospective population-based study in Alberta, Canada (population 4.4 million), where there have been approximately 1550 hospital admissions for COVID-19, to determine the impact of COVID-19 on hospital admissions and emergency department (ED visits), following initiation of a public health emergency act on March 15, 2020. Methods We used multivariable negative bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
128
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 14 publications
11
128
0
1
Order By: Relevance
“…An initial dip in admissions occurred in April 2020, soon after the WHO declared COVID-19 a pandemic. In that period, Croatia experienced a 51% drop in hospital admissions, a trend also observed to varying degrees in other countries, across a number of medical specialties and emergency department visits (9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussion Observationsmentioning
confidence: 89%
See 1 more Smart Citation
“…An initial dip in admissions occurred in April 2020, soon after the WHO declared COVID-19 a pandemic. In that period, Croatia experienced a 51% drop in hospital admissions, a trend also observed to varying degrees in other countries, across a number of medical specialties and emergency department visits (9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussion Observationsmentioning
confidence: 89%
“…There is however, evidence from international sources to support the argument that patient reluctance to attend hospitals could be a major contributing factor. For example, a number of studies on emergency department (ED) admissions during the COVID-19 pandemic report reductions in both daily attendances and surgical admissions through EDs, indicating that patients may not be presenting for needed care ( 10 , 12 , 13 , 26 ). Such patient behavior was investigated in an Italian study ( 27 ) which found that 32% of the cohort surveyed, faced delays in scheduled services, 12% refused to attend scheduled services for fear of contagion, 6% avoided health services despite the onset of an acute issue, and 1.5% avoided EDs when in need.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the number of patients' visits and admissions in the USA [98] revealed a decrease in ER visits, with an increase in hospital admissions. However, another study in Alberta [99] perceived decreased admissions and ER visits to the hospital, despite the low volume of COVID-19 hospital admissions.…”
Section: The Efficiency and Effectiveness Dimension In Covid-19mentioning
confidence: 92%
“…1 , the characteristics of COVID-19 and the initial surge in Seattle led to the implementation of policies and protocols in both the healthcare system and in the community to control the pandemic. Efforts to control the spread of the disease led to a significant reduction in hospital admissions and ED visits, which led to a reduction in clinical revenue (Rennert-May et al, 2021 ). These efforts adversely impacted the delivery of mental health services initially during the April surge and over the subsequent three months due to the costs of these efforts.…”
Section: Discussionmentioning
confidence: 99%